2008
DOI: 10.1177/0093854808321527
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Misconceptions and False Beliefs in Police and Criminal Psychology

Abstract: Although certainly not alone, the field of police and criminal psychology seems to be an area that is highly susceptible to myths and misinformation. Whether it is the notion that police have higher suicide and divorce rates or that crime rates greatly increase during a full moon, there are many commonly held beliefs that are not supported by scientific evidence. This article discusses research conducted by the author and his students over the past several years to investigate the accuracy of some common belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Snook also observed that ‘this is highly disconcerting because of the potential for severe consequences (e.g., miscarriages of justice) when pseudoscientific practices are employed by the police or when erroneous beliefs guide the consequential decision making that is inherent in police work’ (Snook, 2008, p. 1211). As stated by Aamodt (2008), it is disturbing ‘that not only are many of these beliefs not based on an empirical source, but many are perpetuated in spite of evidence to the contrary’ (p. 1231).…”
Section: Is the Behaviour Analysis Interview Just Common Sense?mentioning
confidence: 99%
“…Snook also observed that ‘this is highly disconcerting because of the potential for severe consequences (e.g., miscarriages of justice) when pseudoscientific practices are employed by the police or when erroneous beliefs guide the consequential decision making that is inherent in police work’ (Snook, 2008, p. 1211). As stated by Aamodt (2008), it is disturbing ‘that not only are many of these beliefs not based on an empirical source, but many are perpetuated in spite of evidence to the contrary’ (p. 1231).…”
Section: Is the Behaviour Analysis Interview Just Common Sense?mentioning
confidence: 99%
“…Such results are not surprising as metaanalyses and other research indicates that when it comes to a variety of issues ranging from personality profiles to suicide rates to the ability to detect deception, law enforcement personnel are similar to the general public (Aamodt 2008;Honig 2007).…”
Section: Resultsmentioning
confidence: 89%
“…For example, books by Jurkanin and Hillard (2006); Territo and Sewell (2007); Wells and Alt (2005) suggest higher than normal rates of divorce for police officers, and Aamodt (2008) reported finding the following statistics on the Internet: & Surveys of police officers continually reflect estimates of divorce rates as high as 75% & Police officers…have a high divorce rate, about second in the nation. & Compared to national averages, police officers have been reported to have…double the divorce rate… & Police officers, for example, face divorce rates averaging between 66 and 75 percent.…”
mentioning
confidence: 99%
“…As far as concerns police officers, they are also subject to cognitive biases and myths as everyone else (Aamodt, 2008;Saunders, 2012). Thus, we can expect that, because of the absence of research on CSA background information, they can hold false beliefs about the relation between these variables and CSA risk.…”
Section: Background Information In Csa Research and Investigationsmentioning
confidence: 99%